Development and characterization of biopolyelectrolytes functionalized with ionic liquids for transdermal drug delivery applications - Barroso, Inês Pires Moedas de Almeida (2015)
Dissertação de Mestrado Integrado em Engenharia Biomédica apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra